Effects of treating helminths during pregnancy and early childhood on risk of allergy‐related outcomes: Follow‐up of a randomized controlled trial. Issue 8 (5th October 2017) - Namara, Benigna; Nash, Stephen; Lule, Swaib A.; Akurut, Hellen; Mpairwe, Harriet; Akello, Florence; Tumusiime, Josephine; Kizza, Moses; Kabagenyi, Joyce; Nkurunungi, Gyaviira; Muhangi, Lawrence; Webb, Emily L.; et al.
Abstract: Background: Helminth infections, common in low‐income countries, may protect against allergy‐related disease. Early exposure may be a key. In the Entebbe Mother and Baby Study, treating helminths during pregnancy resulted in increased eczema rates in early childhood. We followed the cohort to determine whether this translated to increased asthma rates at school age. Methods: This randomized, double‐blind, placebo‐controlled trial, conducted in Entebbe, Uganda, had three interventions. During pregnancy, women were randomized, simultaneously, to albendazole vs placebo and to praziquantel vs placebo. Their children were independently randomized to quarterly albendazole vs placebo from age 15 months to 5 years. We here report follow‐up to age 9 years. Primary outcomes at 9 years were recent reported wheeze, skin prick test positivity (SPT) to common allergens and allergen‐specific IgE positivity to dust mite or cockroach. Secondary outcomes were doctor‐diagnosed asthma and eczema rates between 5 and 9 years, recent eczema, rhinitis and urticaria at 9 years, and SPT and IgE responses to individual allergens. Results: 2507 pregnant women were enrolled; 1215 children were seen at age nine, of whom 1188 are included in this analysis. Reported wheeze was rare at 9 years (3.7%) while SPT positivity (25.0%) and IgE positivity (44.1%) were common. There was no evidence of a treatment effect for any of the three interventions on any of the primary outcomes. Conclusions: Prenatal and early‐life treatment of helminths, in the absence of change in other exposures, is unlikely to increase the risk of atopic diseases later in childhood in this tropical, low‐income setting. Abstract :